Uma crítica à redução utilitária da educação sob a perspectiva da teoria da complexidade de Edgar Morin - Kujawa, João Carlos Dinél (2023)
The fundamentals of education have always been a philosophical, sociological, and pedagogical problem. They indicate how, at certain moments in history, different educational paradigms emerged, as well as unique ways of seeing education and its social function. Throughout the various revolutions and historical reformulations, an educational paradigm based on the modern scientific model emerged and, in general terms, is maintained in education until today. With the advent of the industrial revolution and the recent advancement of neoliberal policies, this scientific and educational paradigm was realized through values directed towards the mastery of nature and technique and a utilitarian-based education, aimed at the market and mere economic growth. With these aspects in view, the research problem of this dissertation is based on the following questions: To what extent can Edgar Morin’s complexity theory become an important conceptual basis for criticizing the reductionism of utilitarian education that is trending today? Can we, from Morin’s theory, substantiate the relevance of an education in a broad sense, aimed at the formation of the human being in its complexity? The general objective of this study is to identify and explore Edgar Morin’s complexity theory as a possible basis for criticizing the technical-utilitarian reductionism that tends to mark current education. At the same time, this thinker seeks elements for the basis of an educational proposal more committed to the complexity of the human condition and society. The research is based on Morin’s theoretical framework and has a qualitative character, guided by the theoretical principles of hermeneutics in relation to the reconstruction and analysis of concepts. As main reference works for study, Morin’s works are used, mainly those that refer to education, such as: The seven necessary knowledge for future education (2018), Teaching to live (2015a) and A well-made head (2015b). Some volumes of the author’s main work are also used, The Method (2007; 2011; 2015d) and finally, with the aim of introducing a little complex thinking, we turn to Morin’s own book Introduction to complex thinking (2015c). This dissertation analyzes current education and also its risks, seeking to understand its shortcomings and deficiencies, in addition to introducing the reader to Morin’s thinking about education and his complexity theory. Criticisms are presented to his theory model and a proposal for an educational reform based on respect for the complex dynamics of human beings, society and science. As results, the study pointed out that Morin’s ideas serve as a counterpoint to utilitarian (and ineffective) education insofar as they converge towards an integral formation that points towards an ethical and scientific education. It was also concluded that science reform and the new science that the author bases serve as a subsidy for a new education aimed at forming a subject prepared for complex life problems